Afrikas größte Hängebrücke in Mosambik – Technische Besonderheiten. Issue 2 (13th November 2018) - Seitz, Joern; Pohl, Martin; Maeiro, Jose
Abstract: Die konventionelle Hängebrücke Maputo‐Katembe in Mosambik ist mit einer Spannweite von 680 m die größte Hängebrücke in Afrika und derzeitige Nr. 63 weltweit. Die Erfahrung der chinesischen Ingenieure mit dieser Bauart zeigt sich darin, dass ca. 30 % der 100 größten Hängebrücken weltweit in den vergangenen 20 Jahren in China gebaut wurden. Der Beitrag erläutert die umfangreichen Arbeiten von den Gründungen bis zur Entfeuchtungsanlage für die Hauptkabel im Zeitraum von Herbst 2014 bis Ende 2018. Abstract: Africa's largest suspension bridge – special technical aspects The conventional suspension bridge Maputo‐Katembe in Mozambique with a main span of 680 m makes it the largest suspension bridge in Africa and the current No. 63 worldwide. Approximately 30 % of the world's 100 largest suspension bridges have been built in China over the past 20 years. This underlines the experience of Chinese engineers in this bridge building segment. The article describes the extensive work from the foundations up to the dehumidification facilities for the main cable from autumn 2014 to the end of 2018.